2011
DOI: 10.3892/etm.2011.317
|View full text |Cite
|
Sign up to set email alerts
|

Low-intensity ultrasound-induced cellular destruction and autophagy of nasopharyngeal carcinoma cells

Abstract: Abstract. Ultrasound therapy, as a non-invasive modality, has been attracting extensive attention in the management of malignant tumors. The present study aimed to investigate low-intensity ultrasound-induced cellular destruction and autophagy in nasopharyngeal carcinoma cells in vitro. Nasopharyngeal carcinoma CNE2 cells were subjected to ultrasound exposure, as tumor model cells, at an intensity of 1.35 W/cm 2 . Cytotoxicity was investigated 24 h after ultrasound treatment. Nuclear damage was observed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Crucially, PI3K/AKT/mTOR is a classical signaling pathway involved in the regulation of autophagy. The activation of class I PI3 kinase (PI3K) can phosphorylate ptdIns(4,5)P2 and form PtdIns (3,4,5)P3 in the plasma membrane. In the meantime, class I PI3 kinase (PI3K) can also recruit protein kinase B and phosphoinositide-dependent protein kinase 1, and the co-recruitment of these two kinases leads to the activation of AKT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crucially, PI3K/AKT/mTOR is a classical signaling pathway involved in the regulation of autophagy. The activation of class I PI3 kinase (PI3K) can phosphorylate ptdIns(4,5)P2 and form PtdIns (3,4,5)P3 in the plasma membrane. In the meantime, class I PI3 kinase (PI3K) can also recruit protein kinase B and phosphoinositide-dependent protein kinase 1, and the co-recruitment of these two kinases leads to the activation of AKT.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that autophagy can be observed in tumor cells during the application of low-frequency ultrasonic to irradiate cells of nasopharyngeal carcinoma and prostate cancer [5,6] . Nevertheless, its role and mechanism has still been uncleared so far.…”
Section: Introductionmentioning
confidence: 99%
“…After incubation, the cells were fixed, dehydrated, and embedded as described in our previous studies. 8,9,[14][15][16] Ultrathin sections (100 nm) were made, stained with uranyl acetate and lead citrate, and then observed under transmission electron microscopy (H-600; Hitachi, Ltd, Tokyo, Japan).…”
Section: Mitochondrial Morphologic Changesmentioning
confidence: 99%
“…Autophagy has been observed in tumor cells during application of low-frequency ultrasound to irradiate nasopha-ryngeal carcinoma cells and prostate cancer cells. 5 , 6 Nevertheless, the role of autophagy and its associated mechanisms of action remain unclear. Autophagy is an evolutionarily conserved process.…”
Section: Introductionmentioning
confidence: 99%